Hubungan Kualitas Pelayanan, Customer Experience, Dan Minat Kunjungan Ulang Pasien Rawat Jalan RS Labuang Baji Makassar (Window of Public Health Journal, 2025)
This study aims to determine the relationship between the dimensions of service quality and customer experience with the intention of revisiting outpatients at Labuang Baji Makassar Regional General Hospital in order to build patient loyalty to the hospital. This study used a quantitative method with a cross-sectional design. The sampling technique employed was accidental sampling, with a population of 5,813 individuals and a sample of 373 respondents. Data collection was carried out through questionnaires, and data analysis used univariate and bivariate analysis with the Chi-Square test. The results showed that most dimensions of service quality had a significant relationship with the intention of revisiting patients. Dimensions that showed a significant relationship included responsiveness (p-value = 0.000), physical evidence (p-value = 0.000), empathy (p-value = 0.010), and reliability (p-value = 0.021). The lack of a significant relationship between assurance (p-value = 0.384) and customer experience (p-value = 0.362) suggests that the hospital should focus on improving these areas to foster confidence and motivate staff to enhance overall service quality. Based on these results, the hospital is advised to maintain and improve the service dimensions that have been good, as well as pay special attention to the assurance and customer experience aspects in order to strengthen patient loyalty and improve the overall quality of service.